Composted Sewage Sludge Enhances Soybean Production and Agronomic Performance in Naturally Infertile Soils (Cerrado Region, Brazil) - Rodrigues Prates, Adrielle [UNESP]; Renee Coscione, Aline; Carvalho Minhoto Teixeira Filho, Marcelo [UNESP]; Gasparoti Miranda, Bruno [UNESP]; Arf, Orivaldo [UNESP]; Hamilton Abreu-Junior, Cassio; Carvalho Oliveira, Fernando; Moreira, Adonis; Shintate Galindo, Fernando [UNESP]; Marcia Pereira Sartori, Maria [UNESP]; He, Zhenli; Dilipkumar Jani, Arun; et al. (Mdpi, 2020)
Naturally infertile soils require large amounts of mineral fertilizers to obtain the desired crop yield. In the Cerrado region of Brazil, there is a need to investigate the potential of organic fertilizers to sustainably increase crop productivity and food security. A field study was conducted over two experimental seasons to evaluate the agronomic effectiveness of composted sewage sludge (CSS) as a fertilizer for soybean cultivation in infertile tropical soils. A 4 x 2 + 2 factorial randomized complete block design was applied with the following treatments: (i) CSS: 5.0, 7.5, 10.0, and 12.5 Mg ha(-1) on a wet basis applied according to two different methods: whole area (WA) or between rows (BR); (ii) comparison with two alternative treatments: a control with no CSS and mineral fertilizer application, and an area treated with conventional fertilizers only. All the treatments were compared in terms of micronutrient concentrations in surface soil and plant leaves, plant development, crop productivity, and yield. Bi- (ANOVA, correlation matrix, and polynomial regression analysis) and multivariate (PCA, principal factor analysis) statistics were applied to determine statistical differences and relationships/observed variability among the treatments. Results showed that at higher CSS-WA rates: (i) soil and leaf micronutrient concentrations increased; (ii) there was an increase in soybean yield by 12 and 20%, respectively, as compared to control and conventional fertilization; (iii) soybean yield was 67% higher than the mean soybean yields for Brazil. Research outcomes confirm the benefits of CSS application on infertile agricultural soils in the Cerrado region, representing a strong alternative source of micronutrients in the CSS with respect to conventional fertilizers.
Keywords: Glycine max (L.) Merrill; byproduct; organic fertilizer; plant nutrition; sewage sludge